PERSEPSI MASYARAKAT TERHADAP PENGEMBANGAN DESTINASI PARIWISATA PANTAI KAHONA - hardi, sukma (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study was conducted to understand the public perception of the development of tourist destination Kahona Beach, Kecamatan Jawai. This study uses a spatial approach with a qualitative and participatory descriptive research type of the local community and Kahona Beach tourist destination managers through observation, interview and documentative. Based on the results of interviews obtained with several local communities and the Kahona Beach resort manager, there are two perceptions. The first impression of the Kahona Beach Destination Manager shows that the Kahona beach is good because it has received support from the village government and the local community. The second perception of the local community indicated that the tourist destination Kahona Beach was good due to its proximity and affordable cost. Besides the positive perceptions, there are also negative perceptions from the community because the road to this area still broken and has received little attention. Based on the perceptions conveyed by the community and tourism destination managers, it can be concluded that there are positive perceptions with the existence of economic factors such as the ability of communities to open up business opportunities through commerce, and the negative perceptions caused by the damaged entrance to the tourist attraction Kahona Beach.